Complementary Diagnostic and Prognostic Contributions of Cardiac Computed Tomography for Infective Endocarditis Surgery. (September 2020) - Wang, Tom Kai Ming; Bin Saeedan, Mnahi; Chan, Nicholas; Obuchowski, Nancy A.; Shrestha, Nabin; Xu, Bo; Unai, Shinya; Cremer, Paul; Grimm, Richard A.; Griffin, Brian P.; Flamm, Scott D.; Pettersson, Gosta B.; et al.
Abstract : Background: Cardiac computed tomography (CT) is emerging as an adjunctive modality to echocardiography in the evaluation of infective endocarditis (IE) and surgical planning. CT studies in IE have, however, focused on its diagnostic rather than prognostic utility, the latter of which is important in high-risk diseases like IE. We evaluated the associations between cardiac CT and transesophageal echocardiography (TEE) findings and adverse outcomes after IE surgery. Methods: Of 833 consecutive patients with surgically proven IE during May 1, 2014 to May 1, 2019, at Cleveland Clinic, 155 underwent both preoperative ECG-gated contrast-enhanced CT and TEE. Multivariable analyses were performed to identify CT and TEE biomarkers that predict adverse outcomes after IE surgery, adjusting for EuroSCORE II (European System for Cardiac operative Risk Evaluation II). Results: CT and TEE were positive for IE in 123 (75.0%) and 124 (75.6%) of patients, respectively. Thirty-day mortality occurred in 3 (1.9%) patients and composite mortality or morbidities in 72 (46.5%). Pseudoaneurysm or abscess detected on TEE was the only imaging biomarker to show independent association with composite mortality or morbidities in-hospital, with odds ratio (95% CI) of 3.66 (1.76–7.59), P =0.001. There were 17 late deaths, and both pseudoaneurysm or abscess detected on CT and fistula detected on CT were the only independent predictors of total mortality during follow-up, with hazards ratios (95% CI) of 3.82 (1.25–11.7), P <0.001 and 9.84 (1.89–51.0), P =0.007, respectively. Conclusions: We identified cardiac CT and TEE features that predicted separate adverse outcomes after IE surgery. Imaging biomarkers can play important roles incremental to conventional clinical factors for risk stratification in patients undergoing IE surgery. Abstract : Supplemental Digital Content is available in the text.